2014
DOI: 10.1039/c3py01364b
|View full text |Cite
|
Sign up to set email alerts
|

An enzymatic biomimetic system: enhancement of catalytic efficiency with new polymeric chiral ionic liquids synthesised by controlled radical polymerisation

Abstract: The controlled radical polymerization of monomeric units containing chiral ionic liquids (CILs) allows the synthesis of intrinsically chiral polymers through a bottom-up design. These polymeric chiral ionic liquids (PCILs) show a well-defined three dimensional structure organized as the result of a complex noncovalent network of hydrogen-bonding contacts driven by the C2 hydrogen atoms of the imidazolium aromatic rings and the OH moieties present in the side functionalities of the main polymeric chain. The exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…The polymer matrix should be capable of providing a suitable chain architecture to locate the catalytic units for efficient chiral induction. In view of this, among a variety of polymeric catalysts [6][7][8][9][10][11][12][13][14] for asymmetric organic reactions, the synthetic polypeptides [11][12][13][14] show promise as an ideal scaffold to construct artificial enzymes because their structural components are similar to those of biological macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer matrix should be capable of providing a suitable chain architecture to locate the catalytic units for efficient chiral induction. In view of this, among a variety of polymeric catalysts [6][7][8][9][10][11][12][13][14] for asymmetric organic reactions, the synthetic polypeptides [11][12][13][14] show promise as an ideal scaffold to construct artificial enzymes because their structural components are similar to those of biological macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that, the helical stabilization was due to chirality induction at anionic site as well as at cationic site in vinyl polymers. 76 Montolio et al demonstrated that CPILs bearing chirality at the cationic cite can induce well organize secondary structure. 77 In this current contribution we have demonstrated the induction of chirality as well as helicity in PILs by introducing chiral amino acids at the anionic site.…”
Section: A Introductionmentioning
confidence: 99%
“…In 2014, Karjalainen et al reported the synthesis and application of new polymeric chiral ionic liquids (PCILs) as artificial aldolase biomimetic systems for the aldol reaction [56]. These polymers were prepared by controlled radical polymerization of monomeric units containing chiral ionic liquids (CILs).…”
Section: Organocatalysed Asymmetric Reactionsmentioning
confidence: 99%